Attitudes, Knowledge, and Risk Perceptions of Women With Breast and/or Ovarian Cancer Considering Testing for BRCA1 and BRCA2 - Bluman, Leslie G.; Rimer, Barbara K.; Berry, Donald A.; Borstelmann, Nancy; Iglehart, J. Dirk; Regan, Katherine; Schildkraut, Joellen; Winer, Eric P. (Journal of clinical oncology, 1999)
PURPOSE: This study examined baseline knowledge, beliefs, and risk perceptions among a group of 200 women with breast and/or ovarian cancer who participated in a trial designed to improve decision making about genetic testing for BRCA1 and BRCA2. PATIENTS AND METHODS: Women were identified by self-referral, physician referral, and tumor registry extraction and invited to participate in a randomized trial in which testing for BRCA1 and BRCA2 was offered free of charge. Subjects completed baseline questionnaires and interviews that assessed knowledge, attitudes, and perceptions of risk of having an alteration in BRCA1 or BRCA2. RESULTS: Sixty percent of women overestimated their chances of having a BRCA1 or BRCA2 mutation compared with estimates from a BRCA1/BRCA2 risk model. Women who have at least three relatives with breast or ovarian cancer were one third (95% confidence interval, 0.2 to 0.6) as likely to overestimate their risk of having a BRCA1 or BRCA2 mutation compared with women who have two or fewer affected relatives. Knowledge was limited about BRCA1 and BRCA2 mutations and cancer risk associated with gene mutations. Eighty-four percent of the women indicated a probable or definite interest in testing. CONCLUSION: A high proportion of the high-risk women in this study had knowledge deficits about BRCA1 and BRCA2 and overestimated their risk of having a mutation. Although some degree of caution should be used in generalizing the results of this study to practice settings, the data provide insight into the challenges clinicians will face in communicating with patients about cancer genetics.